The Effects of Baclofen for the Treatment of Gastroesophageal Reflux Disease: A Meta-Analysis of Randomized Controlled Trials - Shujie Li; Shengying Shi; Feng Chen; Jingming Lin (Gastroenterology Research and Practice)
Objectives. Baclofen can relieve gastroesophageal reflux-related symptoms in healthy subjects and gastroesophageal reflux disease (GERD) patients by reducing the incidence of transient lower esophageal sphincter relaxation. This meta-analysis aimed to evaluate the efficacy and safety of baclofen for the treatment of GERD. Methods. We systematically searched randomized controlled trials published prior to November 2013 from PubMed, Medline, Embase, ScienceDirect, ClinicalTrials.gov, and the Cochrane Central Register of Randomized Controlled Trials. We performed a meta-analysis of all eligible trials. Results. Nine studies were identified with a total of 283 GERD patients and healthy subjects. Comparative analysis provided high quality data supporting the ability of baclofen to promote a short-term decrease in the number of reflux episodes per patient, the average length of reflux episodes, and the incidence of transient lower esophageal sphincter relaxation. No serious adverse events or death events were reported, and there were no significant differences in the overall adverse events between baclofen and placebo. All reported side effects of baclofen were of mild-to-moderate intensity, and the drug was well tolerated. Conclusion. Abundant evidence suggests that baclofen may be a useful approach for the treatment of GERD patients; however, a larger well-designed research study would further confirm this recommendation.